Bacterial Species Associated With Human Inflammatory Bowel Disease and Their Pathogenic Mechanisms - Zhang, Li; Liu, Fang; Xue, Jessica; Lee, Seul A.; Liu, Lu; Riordan, Stephen M. (Frontiers in Microbiology, 2022)
Inflammatory bowel disease (IBD) is a chronic inflammatory condition of the gastrointestinal tract with unknown aetiology. The pathogenesis of IBD results from immune responses to microbes in the gastrointestinal tract. Various bacterial species that are associated with human IBD have been identified. However, the microbes that trigger the development of human IBD are still not clear. Here we review bacterial species that are associated with human IBD and their pathogenic mechanisms to provide an updated broad understanding of this research field. IBD is an inflammatory syndrome rather than a single disease. We propose a three-stage pathogenesis model to illustrate the roles of different IBD-associated bacterial species and gut commensal bacteria in the development of human IBD. Finally, we recommend microbe-targeted therapeutic strategies based on the three-stage pathogenesis model.